Pengaruh Manajemen Perubahan, Dynamic Capabilities dan Green Financing Terhadap Keberhasilan Transformasi Leadership UMKM di Nusa Tenggara Barat Peran Organizational Agility Sebagai Variabel Mediasi - Huda, Nurul; Witjaksono, Andre Dwijanto; Kistyanto, Anang (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of Change Management, Dynamic Capabilities, and Green Financing on the success of Leadership Transformation in MSMEs) in West Nusa Tenggara Province (NTB), and to test the mediating role of Organizational Agility in the relationship. Using a quantitative approach and explanatory research method, this study involved the population of all MSMEs in NTB engaged in the agribusiness, culinary, creative industry, and small manufacturing sectors. A sample of 150 MSMEs was selected using a purposive sampling technique. Data were collected through offline and online questionnaires, Data Analysis Techniques using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that the three independent variables, namely Change Management, Dynamic Capabilities, and Green Financing, have an effect on the success of Leadership Transformation. In addition, Organizational Agility is proven to mediate the influence between the three variables on leadership transformation.